A Review on Recent Progress in Membrane Distillation Crystallization. Issue 1 (6th December 2021) - Wan Osman, Wan Nur Aisyah; Mat Nawi, Normi Izati; Samsuri, Shafirah; Bilad, Muhammad Roil; Wibisono, Yusuf; Hernández Yáñez, Eduard; Md Saad, Juniza
Abstract: Membrane distillation crystallization (MDC) is a promising hybrid separation technology that can play an important role in desalination, mineral recovery from liquid solution as well as in carbon dioxide fixation. MDC combines membrane distillation and crystallizer into one integrated unit that allows excellent recovery of clean water and high purity salt from highly concentrated salts solution (i.e., brine), which is otherwise detrimental when discharged to the environment. The process intensification addresses the limitation of standalone membrane distillation and a standalone crystallizer (i.e., temperature and concentration polarization, membrane properties) when operated as individual technology. This review discusses the fundamental of MDC focused on how the process intensification addresses those standalone units' limitations. Later, MDC's potential applications in addressing some pressing issues such as water scarcity and climate change are also evaluated. Lastly, current trends in the MDC research are discussed to project the required future developments. Abstract : This review focused on how the MDC process intensification improves the limitations of those standalone units' (membrane distillation and crystallization. The potential applications of MDC in addressing some pressing issues of water scarcity and climate change are also evaluated. The current trends in the MDC research are also discussed to project the required future developments.